Retrieval of Linear Foreign Body in a Cat Via Single Enterotomy : A Case Report - Mursaleen Bhat; Raja Aijaz Ahmad; Hakim Athar; Shahid Hussain Dar; Mudasir Bashir Gugjoo; Jalal-u-Din Parrah (The Indian Veterinary Journal, 2024)
A 10-month old female cat was presented with a history of vomiting not responding to any medicinal treatment. Radiography revealed gas distended small intestines. Circular target like appearance of small intestines was found on ultrasonography. The cat was administered IV fluids before being put to anesthesia for exploratory celiotomy. It was noticed that one end of thread was anchored at base of tongue and another end was embedded into jejunal wall. The small intestine plication was found which was relieved once oral end of the thread was released. Single enterotomy was performed to withdraw the thread out of the intestine. Enterotomy incision was closed in an interrupted suture pattern followed by routine closure of celiotomy incision.